5n+6n^4+3n-8n^4+n=

Simple and best practice solution for 5n+6n^4+3n-8n^4+n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+6n^4+3n-8n^4+n= equation:

Simplifying
5n + 6n4 + 3n + -8n4 + n = 0

Reorder the terms:
5n + 3n + n + 6n4 + -8n4 = 0

Combine like terms: 5n + 3n = 8n
8n + n + 6n4 + -8n4 = 0

Combine like terms: 8n + n = 9n
9n + 6n4 + -8n4 = 0

Combine like terms: 6n4 + -8n4 = -2n4
9n + -2n4 = 0

Solving
9n + -2n4 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), 'n'.
n(9 + -2n3) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(9 + -2n3)' equal to zero and attempt to solve: Simplifying 9 + -2n3 = 0 Solving 9 + -2n3 = 0 Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2n3 = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2n3 = 0 + -9 -2n3 = 0 + -9 Combine like terms: 0 + -9 = -9 -2n3 = -9 Divide each side by '-2'. n3 = 4.5 Simplifying n3 = 4.5 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

n = {0}